Internationaler Kunstmarkt Köln 1975. - von Butlar, Herbert Freiherr (Köln : Messe- und Ausstellungs-Ges.m.b.H., 1975)
Antes, Horst ; Baselitz, Georg ; Bill, Max ; Brehmer, Klaus-Peter ; Gauguin, Paul ; Hamilton, Richard ; Hockney, David ; Johns, Jasper ; Kandinsky, Wassily ; Kirchner, Ludwig ; Kollwitz, Kathe ; Lehmbruck, Wilhelm ; Man Ray ; Munch, Edvard ; Nagel, Peter ; Nesch, Rolf ; Nolde, Emil ; Picasso, Pablo ; Richter, Gerhard ; Roth, Dieter ; Schmidt-Rottluff, Karl ; Schoonhoven, Jan ; Warhol, Andy
Internationaler Kunstmarkt Köln 1975, 6-10 Nov '75
Duits
boek